2022
DOI: 10.3389/fimmu.2022.805451
|View full text |Cite
|
Sign up to set email alerts
|

The Lineage Differentiation and Dynamic Heterogeneity of Thymic Epithelial Cells During Thymus Organogenesis

Abstract: Although much progress has been made recently in revealing the heterogeneity of the thymic stromal components, the molecular programs of cell lineage divergency and temporal dynamics of thymic epithelial cell (TEC) development are largely elusive. Here, we constructed a single-cell transcriptional landscape of non-hematopoietic cells from mouse thymus spanning embryonic to adult stages, producing transcriptomes of 30,959 TECs. We resolved the transcriptional heterogeneity of developing TECs and highlighted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 102 publications
5
9
0
Order By: Relevance
“…Though both of these approaches have shown the identity of the main TEC populations, many unknown TEC subtypes, in particular, thymus tuft cells, were identified by scRNA-seq in both mice ( 62 , 92 ) and humans ( 63 ). In the recent study authors additionally identified a population of Bpifa1 + Plet1 + mTECs that was preserved during thymus organogenesis in mice, and these mTECs highly expressed tissue-resident adult stem cell markers ( 93 ). Depending on the levels of MHCII and CD80, mTECs are broadly subdivided into mTECs lo ( Cldn4 , lower levels of HLA class II) and mTECs hi ( Spib, Aire, Fezf2 , higher levels of HLA class II).…”
Section: Thymic Epithelial Cellsmentioning
confidence: 99%
“…Though both of these approaches have shown the identity of the main TEC populations, many unknown TEC subtypes, in particular, thymus tuft cells, were identified by scRNA-seq in both mice ( 62 , 92 ) and humans ( 63 ). In the recent study authors additionally identified a population of Bpifa1 + Plet1 + mTECs that was preserved during thymus organogenesis in mice, and these mTECs highly expressed tissue-resident adult stem cell markers ( 93 ). Depending on the levels of MHCII and CD80, mTECs are broadly subdivided into mTECs lo ( Cldn4 , lower levels of HLA class II) and mTECs hi ( Spib, Aire, Fezf2 , higher levels of HLA class II).…”
Section: Thymic Epithelial Cellsmentioning
confidence: 99%
“…Recent single cell sequencing resources demonstrating the diversity of human thymus tissue are incongruous with our current framework of thymus structure and organization [7][8][9][10][11][12][13][14][15][16][17][18][19] which describes a general migratory path a thymocyte takes through the cortex and medulla during conventional αβT cell development. Recent spatial transcriptomic sequencing of human fetal and postnatal thymus has demonstrated that a deeper granularity of thymic niches is present within the tissue and that these niches evolve during fetal development to support different waves of non-conventional T cells 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised clustering identified 7 main clusters of epithelial cells (Fig. S3A), which we annotated according to in vivo datasets (Baran-Gale et al, 2020; Bautista et al, 2021; Bornstein et al, 2018; Gao et al, 2022; Nusser et al, 2022; Park et al, 2020): ‘early cTECs’, ‘cTECs’, ‘early mTECs’, ‘pre-Aire mTECs’, ‘Aire and Spink5 mTECs’, ‘tuft-like mTECs’, and ‘adult bipotent progenitor-like’ (Fig. S3B).…”
Section: Resultsmentioning
confidence: 99%
“…Although thymic epithelial organoids recapitulate many key organoid features such as cell population diversity and possibility to be expanded and passaged, maintaining their functionality in the long term remains challenging. This is probably linked to some niche factors missing in the current relatively minimal culture conditions, which over time either generally prevent functionality to be maintained or enrich for specific subsets that might lack functionality (Gao et al, 2022). Future work including single-cell transcriptomic analysis of the organoids will most likely help identify yet unexplored but necessary niche factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation